Crescent moons and pointed minarets a Muslim book of shapes - Khan, Hena; Amini, Mehrdokht (San Francisco Chronicle Books, 2018)
In simple rhyming text a young Muslim girl guides the reader through the traditions and shapes of Islam
English stories
2
Keywords: Islam -- Customs and practices -- Juvenile fiction; Muslims -- Juvenile fiction; Shapes -- Juvenile fiction; Islam -- Customs and practices -- Fiction; Muslims -- Fiction; Shape -- Fiction; Stories in rhyme; Stories in rhyme